Conception of Polygamy: A Comparative Study of Muhammad ‘Abduh and Faqihuddin Abdul Kodir - Nabielah Rahmi, Mutiara Balqis; Jamilah, Jamilah (IJISH (International Journal of Islamic Studies and Humanities), 2024)
The discourse on polygamy in Islamic law encompasses diverse perspectives. Muhammad 'Abduh and Faqihuddin Abdul Kodir are two figures known for their gender-friendly paradigm for understanding fiqh munākaḥāt, especially polygamy. Both are contemporary scholars with different backgrounds. This study aims to analyze the thoughts of Muhammad 'Abduh and Faqihuddin Abdul Kodir as well as the similarities and differences in their views on polygamy. The research method used is descriptive-analytic which explains the ijtihād background of each figure with a comparative approach. The results show the similarities between 'Abduh and Faqihuddin in three categories: the style of interpretation is tafsīr bi al-ra'y, the dominant method of interpretation is munāsabah al-āyah with verses 2 and 129 al-Nisā' and includes women's experiences, and both prohibit polygamy that leads to harm.. The differences are also divided into three categories; 'Abduh's paradigm is al-db wa al-ijtimā’ī while Faqihuddin mafhūm mubādalah, 'Abduh correlates verse 3 of al-Nisā' with verses 2 and 129 while Faqihuddin with verses 2, 128, 129, and 130, and differences in the characteristics of writing 'Abduh who tends to interpret words and Faqihuddin tends to interpret the wording of the verse as a whole.